Desenvolvimento e validação de uma escala de auto-eficácia alimentar - Poínhos, Rui (2013)
Self-efficacy refers to the beliefs in the ability to organise and implement the action plans needed to achieve a certain result and the feeling of control over the behaviours and environment. It determines the initiation, maintenance and cessation of strategies or behaviours, being a good predictor of eating behaviour. Despite its potential in terms of research, prognosis and evaluation of interventions, we are unaware of instruments to assess global features of food self-efficacy validated for the Portuguese population. The aim of this work is to develop and validate a scale to assess general features of food self-efficacy ("Escala de Auto-Eficácia Alimentar Global"). We evaluated a sample of 276 higher education students, and the analysis was performed separately for the subsamples of females and males. The items were created through the adaptation of the six items of the self-efficacy subscale of the "Inventário Clínico de Auto-Conceito" (Serra, 1986). The analysis led to the maintenance of five of the six items initially considered. The scale shows an unifactorial structure, and the proportion of total variance explained by the principal components extracted is higher than 64%. It also shows good internal consistency, with values of Cronbach's alpha above 0.85. The study of relations with other measures showed evidence of its convergent and discriminant validities. The "Escala de Auto-Eficácia Alimentar Global" may prove to be an useful tool for the prognosis and the evaluation of interventions related to the change in eating habits.